(untitled) (Hollywood, CA, 2013)
Team up with Team Umizoomi on four fantastic animal missions. Help Milli, Geo, and Bot get Purple Monkey to his new Monkey Jungle home at the zoo, rescue Buster the dog at a construction site, fix the Cuckoo Bears clock, and find all of Farmer Dans missing animals.
Purple monkey mission --
Keywords: Drama; Zoos; Animals; Juvenile films; Zoos; Juvenile films; Animals; Drama; Fiction television programs; DVD-Video discs; Video recordings for the hearing impaired; Childrens television programs; Educational television programs; Animated television programs; Nonfiction television programs